Investigating the effect of electrical and thermal transport properties on oxide-based memristors performance and reliability - Armin Gooran-Shoorakchaly; Sarah S. Sharif; Yaser M. Banad (Scientific Reports)
Abstract Achieving reliable resistive switching in oxide-based memristive devices requires precise control over conductive filament (CF) formation and behavior, yet the fundamental relationship between oxide material properties and switching uniformity remains incompletely understood. Here, we develop a comprehensive physical model to investigate how electrical and thermal conductivities influence CF dynamics in TaOx-based memristors. Our simulations reveal that higher electrical conductivity promotes oxygen vacancy generation and reduces forming voltage, while higher thermal conductivity enhances heat dissipation, leading to increased forming voltage. The uniformity of resistive switching is strongly dependent on the interplay between these transport properties. We identify two distinct pathways for achieving optimal High Resistance State (HRS) uniformity with standard deviation-to-mean ratios ( $$\bar {\sigma }/\bar {\mu }$$ ) as low as 0.045, each governed by different balances of electrical and thermal transport mechanisms. For the Low Resistance State (LRS), high uniformity ( $$\bar {\sigma }/\bar {\mu }$$ ≈ 0.009) can be maintained when either electrical or thermal conductivity is low. The resistance ratio between HRS and LRS shows a strong dependence on these conductivities, with higher ratios observed at lower conductivity values. These findings provide essential guidelines for material selection in RRAM devices, particularly for applications demanding high reliability and uniform switching characteristics.